2005
DOI: 10.1590/s0034-89102005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuación estacional de Aedes aegypti en Chaco, Argentina

Abstract: OBJETIVO: Estudiar la fluctuación estacional de Aedes aegypti y correlacionar su abundancia con factores ambientales. MÉTODOS: Las colectas fueron realizadas entre octubre de 2002 y noviembre de 2003, en la ciudad de Resistencia, província del Chaco, Argentina. Fueron hechos muestreos semanales empleando ovitrampas. El número de huevos colectados fue correlacionado con la temperatura, humedad relativa ambiente, evaporación y precipitaciones registradas en dicha localidad. Se utilizó el test de correlación de P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 4 publications
0
5
1
5
Order By: Relevance
“…However, it should be taken into account that monthly cleaning will have to counteract the continued deposition of new containers serving as potential breeding sites, owing to the large number of people repeatedly depositing their waste in the VLs 4 . Dengue epidemics generally occur in periods of heavy rainfall 5,11 . During these periods, immature forms of A. aegypti are encountered in various containers that are capable of accumulating rainwater, such as vases and plants at cemeteries, swimming pools and native bromeliads 6,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be taken into account that monthly cleaning will have to counteract the continued deposition of new containers serving as potential breeding sites, owing to the large number of people repeatedly depositing their waste in the VLs 4 . Dengue epidemics generally occur in periods of heavy rainfall 5,11 . During these periods, immature forms of A. aegypti are encountered in various containers that are capable of accumulating rainwater, such as vases and plants at cemeteries, swimming pools and native bromeliads 6,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Con relación a la población del insecto trasmisor de la enfermedad y los factores del clima en Chaco Argentina, se encontró una abundancia máxima (70%) de huevecillos de A. aegypti en Noviembre y Diciembre del 2002, a una temperatura de 26.4°C y una precipitación de 270.3mm, en donde la precipitación es el factor que determina la presencia del insecto y el riesgo epidemiológico de la enfermedad con un valor de correlación de r=0.57 (p<0.05), la cual coincide con la aparición de personas infectadas (Stein et al 2005). En Barbados Argentina, se encontró este mismo comportamiento con una correlación máxima de r=0.25 después de siete semanas (Depradine & Lovell 2004).…”
unclassified
“…For example, Micieli & Campos (2003) detected oviposition activity in Salta Province throughout the year, with peaks of abundance in Mar that correlated with precipitation levels. Stein et al (2005) observed oviposition activity for Ae. aegypti from Oct to Jun in Chaco, which also correlated with the timing and amounts of precipitation.…”
Section: Seasonal Oviposition Activity Ofmentioning
confidence: 93%
“…Studies in Argentina have shown that oviposition patterns of Ae. aegypti correlate with temperature, humidity, and precipitation (Domínguez et al 2000;Micieli & Campos 2003;Vezzani et al 2004;Stein et al 2005;Micieli et al 2006); for Tucumán, this relationship has not been established. The aim of our study therefore was to observe the relative abundance and seasonal patterns of oviposition by Ae.…”
Section: Seasonal Oviposition Activity Ofmentioning
confidence: 99%